Efektivitas Modul Bentuk Molekul berbasis PjBL Terintegrasi Augmented Reality terhadap Literasi Digital Peserta Didik - M. Abdul Qiram; Yerimadesi Yerimadesi (MASALIQ, 2025)
The development of digital technology has significantly impacted the field of education, particularly in the creation of interactive and contextual learning media. This study aims to determine the effectiveness of a molecular shape module integrated with Augmented Reality (AR) in enhancing the digital literacy skills of Phase F high school students. A quasi-experimental method was employed using a Nonequivalent Control Group Design. The study population included all Phase F high school students, with sample selection conducted through purposive sampling. The results indicate that the AR-based module is effective in improving students’ digital literacy, as evidenced by an N-gain score of 0.683 in the experimental class, categorized as moderate. Supporting data from teacher observation sheets and digital literacy questionnaires showed an average achievement of 86.26%, classified as effective. The results of the independent sample t-test revealed a significance value (2-tailed) of less than 0.05, indicating a significant difference between the experimental and control classes. Therefore, the AR-integrated molecular shape module is proven to be effective in enhancing students’ digital literacy and contributes to the advancement of technology-based learning that is innovative and responsive to contemporary educational needs.